Indonesian Environmental Law: Environmental Justice System and Enforcement - I NYOMAN NURJAYA (Fakultas Hukum Universitas Mulawarman, 2007)
The essence of the environment is actually the essence of human life. It refers to the air, water, land, forest, river, lake, coast, sea, oil and gas, mining and mineral, flora and fauna (biological diversity) and everything within the earth and natural resources contained therein. It is, therefore, human environment defined as a unity of the spatial entity with all objects, potentials, conditions and living organisms, including man and his behavior, which influence the continuance of the life and welfare of human being and other living organisms. Human environment is naturally a system of life comprising the organic natural environment, inorganic natural environment, social environment, and the man-made environment, which influence the continuity of life and the welfare of human being and other living organism